Comparison of performance between Bank Islam and CIMB Bank from year 2005 to 2009 / Wan Suzana Wan Sulaiman - Wan Sulaiman, Wan Suzana (2011)
This study aims to in making informed decisions by helping structure the decision task through an evaluation of a company’s business environment, its strategies, and its financial position and performance. The main objective of this study is to examine the ratio analysis to general- purpose financial statement and related data to derive estimates and inferences useful in business analysis. A sample of annual report from 2005 to 2009 was chosen for this study. The ratio analysis of company was analyzed in term of financial performance of the company. The performance is obtained in the credit analysis. Financial statement are prepared to meet external reporting obligations and also for decision making purpose. They take part in a main role in setting the framework of managerial decisions. However, the information provided in the financial statements is of vast use in making decision through analysis and interpretation of financial statements. Business analysis is very useful in a wide range of business decisions such as whether to invest in equity or in debt securities, whether to extend credit through short term or long-term loans, how to value a business in initial public offering (IPO), and how to evaluate restructuring including mergers, acquisitions, and divestitures.